KLTL-MCM-41 micro-mesoporous composite as a solid base for the hydrogenation of sugars - Tangale, Nilesh P.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
An approach to the synthesis of KLTL-MCM-41 micro-mesoporous composites of varying SiO2/Al2O3 molar ratio (20-8) was designed by following green technology. The synthesis was based on the recycling of waste mother liquor containing preformed KLTL zeolite crystals and unutilized reagents. The micro-mesoporous composites consist of KLTL zeolite crystals preformed through hydrothermal treatment in the first step. In the second step, the siliceous mother liquor was transformed into mesoporous MCM-41. The physico-chemical properties of the KLTL-MCM-41 micro-mesoporous composites were determined by PXRD, ICP-OES, FTIR, CO2-TPD, Al-27 MAS-NMR, TEM-EDX, HRTEM, and N-2 adsorption-desorption measurements. The mesopores properties of the KLTL-MCM-41 composites depended on the SiO2/Al2O3 molar ratio. The characterization results led to the following conclusions with decreasing SiO2/Al2O3 molar ratio: 1) decreasing order of the mesophase, 2) decreasing wall thickness of the mesopores, and 3) decreasing BET surface area and pore volume. Al-27 MAS-NMR spectra showed that only tetrahedrally coordinated aluminium was contained in zeolite KLTL. Moreover, the total amount and the strength of the basic sites of the KLTL-MCM-41 micro-mesoporous composites owing to the exchangeable potassium content (Al/K ratio approximate to 1) decreased in the order: 8 MMC > 10 MMC > 15 MMC > 20 MMC. The catalytic activity of the synthesized micro-mesoporous samples as a solid base was tested for the hydrogenation of xylose to sugar alcohols